HYDROGEN ISOTOPE FRACTIONATION BETWEEN KAOLINITE AND WATER REVISITED - Gilg H.A.; Sheppard S.M.F. (My University, 1996)
The equilibrium hydrogen isotope fractionation factor (α) between kaolinite and water in the temperature range 330 to 0°C is 1000 ln αkaol-water = ?2.2 ? 106 T?2 ? 7.7. This monotonic expression is based on a combination of experimental data with ?75% of exchange and empirical calibrations. The previously proposed and widely accepted complex fractionation expression is considered to reflect the role of surface and intersite fractionation effects in the low percent of exchange experiments (Liu and Epstein, 1984), and incorrect δD water values for the empirical values (Lambert and Epstein, 1980). There is no measurable fractionation between dickite and kaolinite. The temperature dependence of the kaolinite-water hydrogen isotope fractionation factor can probably be used as a model for other phyllosilicate-water systems below 350°C.